2(sin 6+cos6) - 3(sin4+cos4)+1 = 0, Mathematics

2(sin 6?+cos6?) - 3(sin4?+cos4?)+1 = 0

Ans:    (Sin2?)3  + (Cos2?)3-3 (Sin4?+(Cos4?)+1=0

Consider (Sin2?)3  +(Cos2?)3

⇒(Sin2?+Cos2?)3-3 Sin2?Cos2?( Sin2?+Cos2?)

= 1- 3Sin2? Cos2?

Sin4?+Cos4?(Sin2?)2+(Cos2?)2

= (Sin2?+Cos2?)2-2 Sin2? Cos2?

= 1- 2 Sin2? Cos2?

= 2(Sin6?+Cos6?)-3(Sin4?+Cos4?) +1

= 2 (1-3 Sin2? Cos2?)-3 (1-2 Sin2?+Cos2?)+1

 

Posted Date: 4/9/2013 1:51:53 AM | Location : United States







Related Discussions:- 2(sin 6+cos6) - 3(sin4+cos4)+1 = 0, Assignment Help, Ask Question on 2(sin 6+cos6) - 3(sin4+cos4)+1 = 0, Get Answer, Expert's Help, 2(sin 6+cos6) - 3(sin4+cos4)+1 = 0 Discussions

Write discussion on 2(sin 6+cos6) - 3(sin4+cos4)+1 = 0
Your posts are moderated
Related Questions
Millie purchased six bottles of soda at $1.15 each. How much did she pay? To ?nd out the total cost of six bottles, you must multiply the cost per bottle through 6; $1.15 × 6 =

Write an algebraic expression for “Julie runs three miles less than twice the number of miles,

A Solid toy in the form of a hemisphere surmounted by the right circular cone of height  2cm  and  diameter  of  the  base  4  cm .If  a right  circular  cylinder circumscribes the

i have discovered a formula for finding the radius at any point of the graph have i done a good job

I want to complete my assignment, please explain me what is Inequalities?

Graph  ( x + 1) 2 /9 -( y - 2) 2 /4 =1 Solution It is a hyperbola. There are in fact two standard forms for a hyperbola.  Following are the basics for each form. H

Explain Fermats Last Theorem? How to solve problems under Fermats Last Theorem?

Projections The good way to understand projections is to see a couple of diagrams. Thus, given two vectors a → and b → we want to find out the projection of b → onto a → . T

Verify Liouville''s formula for y "-y" - y'' + y = 0 in (0, 1) ?

Q. a(b - c)x^2 + b(c - a)x + c(a - b) = 0 has equal roots then b = ? Ans: Condition that a quadratic equation ax² + bx + c = 0 has equal roots is: Its discriminant, b² - 4ac = 0 A